Effect of Binder Content and Active Filler Selection on Foamed Bitumen Mixtures: Western Australia Experience - Jitsangiam, Peerapong; Huan, Yue; Siripun, Komsun; Leek, Colin; Nikraz, Hamid (Chinese Society of Pavement Engineering, 2012)
Many factors affect the strength and durability of foamed bitumen treated materials, such as binder content, active filler type and content, aggregate composition and gradation, moisture content, compaction effort, and curing regime. This preliminary study investigates the effects of bitumen and active filler on standard mechanical test results. The results failed to demonstrate any consistent trend with bitumen content variation; however, four percent foamed bitumen appears an optimum value in some cases. The addition of cement always resulted in the highest mechanical performance, compared with the addition of hydrated lime and quicklime.